Evaluation and training of Executive Functions in genocide survivors. The case of Yazidi children. Issue 5 (20th February 2019) - Pellizzoni, Sandra; Apuzzo, Gian Matteo; De Vita, Chiara; Agostini, Tiziano; Passolunghi, Maria Chiara
Abstract: Executive Functions (EFs) development is critically affected by stress and trauma, as well as the socioeconomic context in which children grow up (Welsh, Nix, Blair, Bierman, & Nelson, 2010, Journal of Educational Psychology, 102, 43–53). Research in this field is surprisingly lacking in relation to war contexts. This study represents a first attempt at addressing this topic by evaluating EFs in Yazidi children. The Yazidi community is an ethnic and religious minority living in Iraq. From August 2014 onwards, the Yazidi community has been the target of several atrocities perpetrated by ISIS and described as genocide by the international community at large. The University of Trieste, thanks to a program financed by the Friuli Venezia Giulia Region, developed a study aimed at (a) evaluating hot and cool EFs in children living in a war context and (b) developing a specific training method to enhance hot and cool EFs in Yazidi children of preschool age ( N = 53). Data related to this group of children were compared with a sample of typically developing Italian children randomly assigned to either an EFs training group ( N = 55) or a passive control group ( N = 51). Results indicate different baselines in EFs in Yazidi and Italian samples and a significant effect of the program on both trained groups, especially in tasks measuring hot EFs. Data are discussed in terms of hot and cool EFs in children growing in adverse environments, as well as the evaluation of educational and developmental opportunities to prevent children who survived genocide from becoming a 'lost generation'. A video abstract of this article can be viewed at https://youtu.be/7t_08TbxR_8 . Abstract : The present research focused on early assessment and training of hot and cool EFs in Yazidi children. Results, indicating different baselines in EFs in Yazidi and control samples and a significant effect of the training program, are discussed in terms of developmental opportunities.